Ist unsere Heimat im Himmel?: Überlegungen zur Semantik von πολιτευμα in Phil 3,20 - Förster, Hans (Early christianity, 2014)
Within the letter of Paul to the Philippians a hapax legomenon within the New Testament occurs (πολιτευμα). The meaning of this word – and therefore of the entire passage – is disputed. It seems, however, that Paul used deliberately a word with no exact definition in order to convey his message to his readers. This contention would also influence the translation of the verse in question (Phil 3,20).